Role of Helicobacter pylori in ulcer healing and recurrence of gastric and duodenal ulcers in longterm NSAID users. Response to omeprazole dual therapy. (July 1996) - Bianchi Porro, G; Parente, F; Imbesi, V; Montrone, F; Caruso, I
Abstract : BACKGROUND: The relation between Helicobacter pylori infection and non-steroidal anti-inflammatory drug (NSAID)-associated peptic ulcers remains unclear; in particular, it is not known whether H pylori plays a part in the healing and recurrence of these ulcers. AIMS: To evaluate prospectively in a consecutive series of arthritis patients receiving longterm NSAID treatment the prevalence of peptic ulcer as well as the effect of H pylori eradication on the healing and recurrence of gastric and duodenal ulcer found. PATIENTS: Some 278 consecutive patients underwent gastroscopy with multiple biopsies of the gastric antrum and corpus for histological examination and rapid urease test. One hundred peptic ulcers (59 gastric ulcers, 39 duodenal ulcers, and two gastric ulcers concomitant with a duodenal ulcer) were found. Seventy per cent of these ulcers were H pylori positive. METHODS: According to their H pylori status, ulcer patients were randomised to one of the following treatments: H pylori negative ulcers received omeprazole 20 mg twice daily for four to eight weeks, whereas H pylori positive lesions were treated with omeprazole 20 mg twice daily plus amoxycillin 1 g twice daily (the second of these for the first two weeks) or omeprazole alone for four to eight weeks while continuing NSAID therapy. Patients with healed ulcers were endoscopically followed up for six months after stopping antiulcer therapy while continuing NSAIDs. RESULTS: Endoscopic healing rates for gastric and duodenal ulcers in the three different groups were similar both at four and eight weeks. H pylori eradication did not influence healing, which occurred in 14 of 20 (70%) of patients in whom H pylori was eradicated, compared with 14 of 17 (82%) of patients with persistent infection. Cumulative recurrence rates at six months did not statistically differ among the three different groups (27% in H pylori negative, 46% in H pylori positive, and 31% in those where H pylori was eradicated during the healing phase), although a numerical trend in favour of a higher recurrence rate in infected patients was evident. CONCLUSIONS: H pylori eradication does not confer any significant advantage on the healing of gastric and duodenal ulcers associated with longterm NSAID use. It remains to be established with certainty whether eradication may be helpful in the reduction of recurrence in a specific subset of NSAID associated ulcer.